2016
DOI: 10.4149/bll_2016_082
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum corticosteroids in HELLP syndrome – standard to prompt recovery

Abstract: OBJECTIVES: To perform a complex review of HELLP syndrome and its treatment from up to date scientifi c literature. Study of the interresting treatement regime of the patient. METHODS: Complex analysis of the syndrome, systematic search of medical scientifi c databases and Slovak Medical Library. Analysis of the life threatening state of the patient, retrospective analysis of the diagnostics, treatment, acute management, complications and clinical results. RESULTS: According to up to date literature and our go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
3
0
1
Order By: Relevance
“…In SR during years 2012-2014 vaginal delivery had only 10 (10.8 %) patients with HELLP syndrome and 83 (89.2 %) had caesarean section. Gabor et al in his case report (15) wrote , that patient with HELLP syndrome was primigravida with gestational diabetes mellitus. The onset of HELLP syndrome was on 35th weeks of gestation and she had caesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…In SR during years 2012-2014 vaginal delivery had only 10 (10.8 %) patients with HELLP syndrome and 83 (89.2 %) had caesarean section. Gabor et al in his case report (15) wrote , that patient with HELLP syndrome was primigravida with gestational diabetes mellitus. The onset of HELLP syndrome was on 35th weeks of gestation and she had caesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, evaluation of the fetus’s condition in the uterus and timely termination of pregnancy are performed in HELLP syndrome. 2,3 Among them, glucocorticoids play a vital role in treating HELLP syndrome, but this treatment has been controversial in the past 20 years. Some studies have shown that high-dose hormonotherapy is effective for alleviating the maternal and fetal prognoses and accelerating postnatal recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Demgegenüber gibt es auch andere Arbeitsgruppen, die den Nutzen der Glukokortikoid-Applikation in Frage stellen [17]. Bei postpartalem HELLP-Syndrom oder anhaltend pathologischen Laborwerten kann die Gabe von Glukokortikoiden auch nach der Entbindung erwogen werden [18]. Wir führten bei unserer Patientin eine Eklampsie-Prophylaxe mit Magnesiumsulfat postpartal durch.…”
Section: Introductionunclassified